2010
DOI: 10.5194/amt-3-1075-2010
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Ionization Mass Spectrometer for ambient measurements of Ammonia

Abstract: Abstract. This study presents a chemical ionization mass spectrometer (CIMS) for fast response, in-situ measurements of gas phase ammonia (NH 3 ). The NH 3 background level detected with the CIMS ranged between 0.3-1 ppbv, with an uncertainty of 30 pptv under optimized conditions. The instrument sensitivity varied from 4-25 Hz/pptv for >1 MHz of reagent ion signals (protonated ethanol ions), with a 30% uncertainty estimated based on variability in calibration signals. The CIMS detection limit for NH 3 was ∼60 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…One of the major technical challenges of measuring these sticky base molecules is to efficiently reduce the "CIMS background" signals, which are different by definition from impurity background concentrations in the nucleation reactor, and these background signals must be taken into account, as discussed in detail in Benson et al (2010). The CIMS sensitivity for NH 3 was about 3-4 Hz pptv −1 for >1 MHz of reagent ion signals, with 30 % uncertainties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major technical challenges of measuring these sticky base molecules is to efficiently reduce the "CIMS background" signals, which are different by definition from impurity background concentrations in the nucleation reactor, and these background signals must be taken into account, as discussed in detail in Benson et al (2010). The CIMS sensitivity for NH 3 was about 3-4 Hz pptv −1 for >1 MHz of reagent ion signals, with 30 % uncertainties.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental tests have shown that whereas adsorption of NH 3 is most effective on stainless steel material, NH 3 adsorption is minimal on fluorinated ethylene propylene (FEP) or perfluoroalkoxy (PFA) Teflon surfaces Neuman et al, 2003;Nowak et al, 2002Nowak et al, , 2006Yokelson et al, 2003). Such impurities are one of the major limitations of nucleation studies, especially considering that NH 3 can increase nucleation of H 2 SO 4 aerosols (Ball et al, 1999;Benson et al, 2009Benson et al, , 2010Berndt et al, 2010). It is also possible that amines can co-exist with NH 3 , as they both have similar sources (Ge et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, NH 3 atmospheric levels range from a few hundreds of pptv to several ppbv (Li et al, 2006;Benson et al, 2010). Lower values could usually not be reported because of detection limitations.…”
Section: Atmosmentioning
confidence: 99%
“…Conventional offline NH 3 sensors (passive filters, denuders and ion chromatography) often have sufficient sensitivity (< 1 ppbv NH 3 ), but have long integration times, lack the requisite selectivity and are labor intensive to analyze (Fehsenfeld et al, 2002;von Bobrutzki et al, 2010;Ellis et al, 2011). Chemical ionization mass spectrometry (CIMS) NH 3 instruments have high time resolution (seconds), selectivity and extremely high sensitivity (< 100 pptv NH 3 ), but require large power consumption (kW) and space (multiple instrument racks) (Nowak et al, 2007;Benson et al, 2010;Sintermann et al, 2011). Laser absorption spectrometers for gas-phase NH 3 have been developed for real-time, high-sensitivity and selective detection.…”
Section: J Miller Et Al: Open-path Qcl-based Ammonia Sensormentioning
confidence: 99%